Romania Foreign Trade in Global Recession, Revealed by the Extended Method of Exchange Rate Indicators - Gheorghe Săvoiu; Vasile Dinu; Laurenţiu Tăchiciu (Amfiteatru Economic Journal, 2012)
In this article the authors propose an extended method for assessing foreign trade, which is capitalized on in the analysis of foreign trade/external marketing, under the influence of two of the most difficult recession of the Romanian economy, placed in the last interwar decade and in the first decade of the new millennium. The selection of the periods for the analysis, despite and beyond the methodological shortcomings concerning the provision of statistical comparability, which is relatively overcome by the advantages of the method, was dictated by the regulator impact of the major recessions in Romanian foreign trade, which offers the possibility to identify a national profile of economic behaviour. The structure of the article includes, after an introductory reference to approaching external marketing in the main economic theories, the first section dealing with the repertoire of foreign trade theories, with main emphasis on the specific contemporary issues and trends, but also a section for detailing the extended method proposed and the original statistical tools that are proposed (from the spread of the mobile rates of the contrary flows, to the indices and coefficients of the Hirschman and Gini-Struck type in curve ABC), and of the databases. Once applied in the results section, the extended method manages to quantify the broad outline of a reactive profile, slightly lagging and inertial, of the external marketing / foreign trade of the national economy, in relation to crisis or recession in both time analyses, which is relatively stable for eight decades, providing space for comments that allow greater macro-economic self-awareness. The main final remark shows that a small starting gap, apparently favourable, of Romanian foreign trade, in response to crisis or recession type phenomena, cannot however compensate the inertial trend of these cyclic phenomena, which is slightly longer than one year, and whose negative impact is strongly felt and amplified.
Keywords: C46; E31; O24; N74; P22; P33; 330; method of exchange indicators; foreign/international trade; mercantilism; spread of mobile rates; Hirschman and Gini-Struck indices and coefficients in ABC curve